2008
DOI: 10.1128/jvi.02353-07
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Protease Cleavage Sites within and Flanking Human Immunodeficiency Virus Type 1 Transframe Protein p6* for Spatiotemporal Regulation of Protease Activation

Abstract: The human immunodeficiency virus type 1 (HIV-1) protease (PR) has recently been shown to be inhibited by its propeptide p6* in vitro. As p6* itself is a PR substrate, the primary goal of this study was to determine the importance of p6* cleavage for HIV-1 maturation and infectivity. For that purpose, short peptide variants mimicking proposed cleavage sites within and flanking p6* were designed and analyzed for qualitative and quantitative hydrolysis in vitro. Proviral clones comprising the selected cleavage si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 63 publications
6
49
0
Order By: Relevance
“…Interestingly, the autoprocessing of a truncated Gag-PR precursor was clearly accelerated when the p6* sequence was deleted, leading to the proposal that the active site of the PR might be less accessible in the presence of p6* (26). Further observations that p6* itself is sequentially cleaved by the PR (1,7,22,23,24,30,31,32,41) strengthened the hypothesis that the transframe protein contributes to spatiotemporal activation of the PR. Indeed, we and others have previously shown that the PR needs to be released from the flanking p6* residues to be capable of completing all virusassociated processing steps (24,27,36).…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…Interestingly, the autoprocessing of a truncated Gag-PR precursor was clearly accelerated when the p6* sequence was deleted, leading to the proposal that the active site of the PR might be less accessible in the presence of p6* (26). Further observations that p6* itself is sequentially cleaved by the PR (1,7,22,23,24,30,31,32,41) strengthened the hypothesis that the transframe protein contributes to spatiotemporal activation of the PR. Indeed, we and others have previously shown that the PR needs to be released from the flanking p6* residues to be capable of completing all virusassociated processing steps (24,27,36).…”
mentioning
confidence: 60%
“…Further observations that p6* itself is sequentially cleaved by the PR (1,7,22,23,24,30,31,32,41) strengthened the hypothesis that the transframe protein contributes to spatiotemporal activation of the PR. Indeed, we and others have previously shown that the PR needs to be released from the flanking p6* residues to be capable of completing all virusassociated processing steps (24,27,36). The potential of p6* to regulate PR activity has been further corroborated by our finding that recombinant p6* protein comprising a free accessible carboxyl terminus is a potent inhibitor of the mature PR in vitro (28).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…In line with this evidence, a complete deletion of p6* enhances protease-mediated proteolytic processing (511). (ii) Cleavages on incorrect p6* positions may significantly reduce the maturation of viral particles, highlighting the importance of accurate cleavages at p6* for protease activation (512). (iii) Although GagPol precursors lacking the p6* region could be incorporated into HIV-1 particles, p6* exerts negative regulation on protease dimerization, and it is indispensable for protease-mediated maturation (513).…”
Section: Protease-gag/gagpol Interactionmentioning
confidence: 51%